2020
DOI: 10.3390/pharmaceutics12070597
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The Enhanced Cytotoxic and Pro-Apoptotic Effects of Optimized Simvastatin-Loaded Emulsomes on MCF-7 Breast Cancer Cells

Abstract: Statins, including simvastatin (SMV), are commonly used for the control of hyperlipidaemia and have also proven therapeutic and preventative effects in cardiovascular diseases. Besides that, there is an emerging interest in their use as antineoplastic drugs as demonstrated by different studies showing their cytotoxic activity against different cancer cells. In this study, SMV-loaded emulsomes (SMV-EMLs) were formulated and evaluated for their cytotoxic activity in MCF-7 breast cancer cells. The emulsomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 58 publications
5
29
0
Order By: Relevance
“…As showed in Figure 4 , the IC50 of FBX-R (21.4 ± 3.0 µM) was significantly decreased by the encapsulation of the drug into the EMLs (5.4 ± 3.1 µM, about 4-fold lower), underlining the enhanced therapeutic potential of the optimized formulation in counteracting cancer cells proliferation. These results are in agreement with recent data showing the ability of EMLs-based formulations to enhance the cytotoxic effects of another “repositioned drug” (simvastatin) on breast cancer cells [ 33 ]. Taking into consideration the frequently reported adverse events related to the use of this drug [ 46 ], the development of new formulations able to boost its therapeutic effect, reducing the effective dose of FBX could be of great relevance for future translational studies in cancer patients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…As showed in Figure 4 , the IC50 of FBX-R (21.4 ± 3.0 µM) was significantly decreased by the encapsulation of the drug into the EMLs (5.4 ± 3.1 µM, about 4-fold lower), underlining the enhanced therapeutic potential of the optimized formulation in counteracting cancer cells proliferation. These results are in agreement with recent data showing the ability of EMLs-based formulations to enhance the cytotoxic effects of another “repositioned drug” (simvastatin) on breast cancer cells [ 33 ]. Taking into consideration the frequently reported adverse events related to the use of this drug [ 46 ], the development of new formulations able to boost its therapeutic effect, reducing the effective dose of FBX could be of great relevance for future translational studies in cancer patients.…”
Section: Discussionsupporting
confidence: 93%
“…Febuxostat (FBX) is an inhibitor of xanthine oxidase enzyme currently used for the treatment of hyperuricemia in subjects with gout [ 35 ]. It has been shown that this drug is practically insoluble in water, while its solubility increases in solvents such as dimethylsulfoxide [ 36 ], and the use of drug delivery systems such as EMLs [ 33 , 37 ] could represent a powerful tool to increase its solubility and, at the same time, improve the drug dissolution rate, then enhancing the clinical efficacy of this drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations